ANALISIS FAKTOR YANG MEMPENGRUHI KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS VIII E SMPN 1 KARAWANG - Agustin, Cindy; Sitika, Achmad Junaedi; Nurhasan, Nurhasan; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2025)
In the learning process, especially in the subject of Islamic religious education, activity is very much needed by students to achieve a learning goal. Apart from that religious education is also a very important subject that can guarantee happiness and well-being both physically, spiritually and socially. So to achieve this, a learning process is needed that involves students actively. When students are passive or only receive from the teacher, there is a tendency to quickly do what has been given. This study aims to determine the learning activeness of VIII E class students in learning Islamic Religious Education, to determine the supporting and inhibiting factors in student learning activeness, and to determine the results achieved in the learning activeness of VIII E class students in the subject of Islamic Religious Education at SMPN 1 Karawang Barat. The research method used in this study is a qualitative method. The population for this study were students of class VIII SMPN 1 West Karawang, totaling 440 students and the sample for this study was students of class VIII E, totaling 36 people.